Genomic Structural Variants Methods and Protocols - Feuk, Lars.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
The completion of a consensus draft sequence for the human genome was the starting point for more thorough investigations of individual genome variation.  The development of array-based strategies made it possible to look at our genome in new ways and for new types of variation to be discovered and characterized. Characterization of copy number variation and other forms of structural genetic variation has highlighted the complexity of human genetic variation and also provided significant insight into the evolution and dynamic nature of our genome. Genomic Structural Variants: Methods and Protocols provides an in-depth description of the developments in our understanding of structural genetic variation and its implications for human disease, from the introduction of microarrays up to current state-of-the-art sequencing strategies. It covers the major technologies used for research and diagnostics as well as web-based resources for variation data, and it then goes into depth regarding specific regions of the genome that differ in variation content. Specific patient groups where copy number variation has been shown to be of great importance are highlighted, and implications for both pre-natal and standard diagnostics are described. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and accessible, Genomic Structural Variants: Methods and Protocols provides complete comprehensive coverage of this burgeoning field.
What Have Studies of Genomic Disorders Taught us about our Genome -- Microdeletion and Microduplication Syndromes -- Structural Genomic Variation in Mental Retardation -- Copy Number Variation and Psychiatric Disease Risk -- Detection and Characterization of Copy Number Variation (CNV) in Autism Spectrum Disorder (ASD) -- Structural Variation in Subtelomeres -- Array Based Approaches in Prenatal Diagnosis -- Structural Variation and its Effect on Expression -- The Challenges of Studying Complex and Dynamic Regions of the Human Genome -- Population Genetic Nature of Copy Number Variation -- Detection and Interpretation of Genomic Structural Variation in Mammals -- Structural Genetic Variation in the Context of Somatic Mosaicism -- Online Resources for Genomic Structural Variation -- Algorithm Implementation for CNV Discovery using Affymetrix and Ilumina SNP Array Data -- Targeted Screening and Validation of Copy Nuber Variations -- High-resolution Copy Number Profiling by Array CGH using DNA Isolated from Formalin-Fixed Paraffin-Embedded Tissues -- Characterizing and Interpreting Genetic Variation from Personal Genome Sequencing -- Massively Parallel Sequencing Approaches for Characterization of Structural Variation.
Keywords: Human genetics; Medical genetics; Human Genetics; Gene Function